User mode choice behavior in public transportation : a systematic literature review - Sua, Abigail Jee Qian; Chua, Hui Na; Khoo, Hooi Ling; Low, Yeh Ching; Lee, Angela Siew Hoong; Maizatul Akmar Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2022)
With the staggering concerns in environmental pollution caused by the transportation industry, researchers have ventured their studies to identify the primary factors that may affect an individuals’ propensity to choose public transportation as more sustainable transportation. Numerous research studies are surrounding this subject; however, no effort has been made to systematically review them for a synthesized analysis. There is also a lack of study in identifying contributing factors that may potentially affect each other to determine the propensity to take public transportation and identify their relationships to each other to provide a guide for future researchers to analyse and consider for future work. With the motivation to tackle the existing research inadequacies, we conducted a study that focuses on using a systematic literature review methodology with validated analyses on existing studies. This study found that demographic factors are the most analysed aspect, followed by transportation, trip-related and environmental. Secondly, our study provides new insight into several contributing factors affecting each other in predicting public transportation ridership. Thirdly, our findings also demonstrate the trends and gaps that occur in different geographical areas. The outcomes of our research present a consolidated view for relevant authorities to cater their strategies tactically according to each geographical area and identify potential opportunities for future research.